Political Tie Heterogeneity and the Impact of Adverse Shocks on Firm Value - Sun, Pei; Mellahi, Kamel; Wright, Mike; Xu, Haoping (Journal of Management Studies, 2015)
ABSTRACTPast research has recognized the contingent value of corporate political ties but largely neglects their heterogeneity. Drawing on the political embeddedness perspective and literature on emerging economy political institutions, we develop hypotheses regarding how political networks comprising managerial and government ownership ties may have different valuation effects in the face of adverse political shocks. Examining stock market responses to an unanticipated, high‐profile political event in China, we find a negative valuation effect of managerial ties to municipal government, but an insignificant effect of government ownership ties. Further, companies combining managerial and ownership ties experienced less post‐shock reduction in market value than those holding only managerial political ties. These findings shed light on the values of different configurations of corporate political ties and inform firms of potential ways to manage ubiquitous political hazards in emerging economies.